2008
DOI: 10.1016/j.jcrs.2008.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Comparative micromorphologic in vitro porcine study of IntraLase and Femto LDV femtosecond lasers

Abstract: The laser cuts of the IntraLase FS and Femto LDV femtosecond lasers were equally smooth and of excellent quality. The standard deviation of the flap thickness was small and equal in both systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 18 publications
3
16
0
1
Order By: Relevance
“…The advantage was evident in improved surface quality of the stromal bed in lamellar keratotomies [4,5]. A study conducted with a new 200-kHz laser (WaveLight UltraFlap -Femtosecond laser) applying 500-nJ pulse energy and 5-μm spot distance showed very smooth intrastromal cuts as judged by scanning electron microscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage was evident in improved surface quality of the stromal bed in lamellar keratotomies [4,5]. A study conducted with a new 200-kHz laser (WaveLight UltraFlap -Femtosecond laser) applying 500-nJ pulse energy and 5-μm spot distance showed very smooth intrastromal cuts as judged by scanning electron microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…For Femto-LASIK, refinement of laser technology was associated with smoother stromal beds [4]. This was demonstrated for flap surfaces in human donor eyes [4] and on porcine tissue for flaps [5] as well as refractive lenticules (own unpublished data). The aim of this study was to investigate the influence of laser settings on surface quality of human corneal lenticules which were extracted during the FLEx procedure using the 200 kHz VisuMax® femtosecond laser system (Carl Zeiss Meditec AG, Jena, Germany).…”
Section: Introductionmentioning
confidence: 92%
“…Recent studies 8,10,11 show that femtosecond lasers may produce smoother surfaces than some mechanical microkeratomes; however, it is not known whether this results in better functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies, however, have not demonstrated such difference in flap morphology between laser platforms. Kermani and Oberheide [17] found that laser cuts made with the Intralase FS 60-kHz and Femto LDV laser systems were equally smooth and of excellent quality. A more recent prospective study by Zhang et al [18] showed that while LASIK flaps made with the Femto LDV were thinner, flap predictability and uniformity otherwise did not differ between the Intralase FS 60-kHz and Femto LDV systems.…”
Section: Femtosecond Lasersmentioning
confidence: 99%